the sum. d^2+d-30/d^2+3d-40 + d^2+14d+48/d^2-2d-48 A. d^2+14d+16 / (d+8)(d-8) B. 2d^2+14d+16/(d+8)(d-8) C. 2d^2+15d+18/(d+8)(d-8)

Question

Asked 10/1/2012 8:04:19 PM

Updated 4/24/2014 12:41:55 AM

1 Answer/Comment

Flagged by yeswey [4/24/2014 12:41:55 AM]

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Question

Asked 10/1/2012 8:04:19 PM

Updated 4/24/2014 12:41:55 AM

1 Answer/Comment

Flagged by yeswey [4/24/2014 12:41:55 AM]

Rating

8

(d^2+d-30)/(d^2+3d-40) + (d^2+14d+48)/(d^2-2d-48)

= (d - 5)(d + 6)/(d + 8)(d - 5) + (d + 6)(d + 8)/(d - 8)(d + 6)

= (d + 6)/(d + 8) + (d + 8)/(d - 8)

= (d + 6)(d - 8)/(d + 8)(d - 8) + (d + 8)(d + 8)/(d - 8)(d + 8)

= (d^2 - 2d - 48)/(d + 8)(d - 8) + (d^2 + 16d + 64)/(d + 8)(d - 8)

= (2d^2 + 14d + 16)/(d + 8)(d - 8)

= (d - 5)(d + 6)/(d + 8)(d - 5) + (d + 6)(d + 8)/(d - 8)(d + 6)

= (d + 6)/(d + 8) + (d + 8)/(d - 8)

= (d + 6)(d - 8)/(d + 8)(d - 8) + (d + 8)(d + 8)/(d - 8)(d + 8)

= (d^2 - 2d - 48)/(d + 8)(d - 8) + (d^2 + 16d + 64)/(d + 8)(d - 8)

= (2d^2 + 14d + 16)/(d + 8)(d - 8)

Added 4/24/2014 12:41:51 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/24/2014 12:43:37 AM]

Solve by graphing.
x2 +2x - 8 = 0 **Weegy:** Solve x2 - 2x - 8 = 0 by graphing. The x intercepts are - Algebra
› Algebra › Coordinate-systemSOLUTION: Solve x2 - 2x - 8 = 0 by graphing. The x intercepts are ? and ?. [ Algebra -> Algebra -> Coordinate-system -> SOLUTION: Solve x2 - 2x - 8 = 0 by ... ] (More)

Question

Expert Answered

Updated 67 days ago|11/26/2022 12:24:35 AM

1 Answer/Comment

x^2 +2x - 8 = 0

(x - 2) ( x + 4) = 0

x = 2, x = - 2

(x - 2) ( x + 4) = 0

x = 2, x = - 2

Added 67 days ago|11/26/2022 12:24:30 AM

This answer has been confirmed as correct and helpful.

Simplify the sum. d^2+d-30/d^2+3d-40 + d^2+14d+48/d^2-2d-48 A. 2d62+15d+18/2d^2+d-88 B. d^2+14d+16 / (d+8)(d-8) C. 2d^2+14d+16/(d+8)(d-8) D. 2d^2+15d+18/(d+8)(d-8) **Weegy:** A. 2d62+15d+18/2d^2+d-88 is the answer. (More)

Question

Expert Answered

Asked 10/1/2012 7:43:29 PM

0 Answers/Comments

Use the Binomial Theorem to expand the binomial. (x + 2y^2)3 A. x3 - 3x^2y2 + 3xy^4 - y^6 B. x3 + 6^x2y2 + 12xy^4 + 8y^6 C. x3 - 6x^2y2 + 12xy^4 - 8y^6 w D. x3 + 3x^2y^2 + 3xy^4 + y6
**Weegy:** C. x3 - 6x^2y2 + 12xy^4 - 8y^6 (More)

Question

Expert Answered

Updated 6/10/2014 11:44:25 PM

1 Answer/Comment

What is the expression in factored form? 16x^2 - 25 A. (4x - 5)2 B. (4x + 5)(-4x - 5) C. (4x + 5)(4x - 5) D. (-4x + 5)(4x - 5)

Question

Not Answered

Updated 7/30/2014 10:03:25 AM

1 Answer/Comment

16x^2 - 25 = (4x + 5)(4x - 5)

Added 7/30/2014 10:03:25 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/30/2014 10:05:16 AM]

Multiply and simplify if possible.v7x(vx-7v7) A. xv7-49vx B.xv7-xv49 C.v7x-49x D. -v42x **Weegy:** the answer is C (More)

Question

Expert Answered

Updated 5/7/2014 9:03:25 PM

1 Answer/Comment

37,268,478

questions answered

There are no comments.